Polymeric Hydrogel Systems as Emerging Biomaterial Platforms to Enable Hemostasis and Wound Healing - Pourshahrestani, Sara; Zeimaran, Ehsan; Kadri, Nahrizul Adib; Mutlu, Nurshen; Boccaccini, Aldo R. (Advanced Healthcare Materials, 2020)
Broad interest in developing new hemostatic technologies arises from unmet needs in mitigating uncontrolled hemorrhage in emergency, surgical, and battlefield settings. Although a variety of hemostats, sealants, and adhesives are available, development of ideal hemostatic compositions that offer a range of remarkable properties including capability to effectively and immediately manage bleeding, excellent mechanical properties, biocompatibility, biodegradability, antibacterial effect, and strong tissue adhesion properties, under wet and dynamic conditions, still remains a challenge. Benefiting from tunable mechanical properties, high porosity, biocompatibility, injectability and ease of handling, polymeric hydrogels with outstanding hemostatic properties have been receiving increasing attention over the past several years. In this review, after shedding light on hemostasis and wound healing processes, the most recent progresses in hydrogel systems engineered from natural and synthetic polymers for hemostatic applications are discussed based on a comprehensive literature review. Most studies described used in vivo models with accessible and compressible wounds to assess the hemostatic performance of hydrogels. The challenges that need to be tackled to accelerate the translation of these novel hemostatic hydrogel systems to clinical practice are emphasized and future directions for research in the field are presented.
CRIS-Team Scopus Importer:2020-09-25
Keywords: adhesives; hemostasis; hemostats; injectable hydrogels; wound healing